Formulation optimization of a sucrose-free probiotic dark chocolate; rheological characteristics and viability of Saccharomyces boulardi - Haniyeh Rasouli Pirouzian; Hadi Pourjafar; Fereshteh Ansari; Nezam Armand; Seid Mahdi Jafari (Current Research in Food Science)
The use of polyols as sucrose-replacer in chocolate formulation has increased in the last years because of the high occurrence of the metabolic syndrome. Furthermore, chocolate is a qualified vehicle of functional ingredients such as probiotics that improve health in people with diabetes. The first objective of this study was to evaluate the optimal formulation of sucrose-free dark chocolate (SFDC) using a mixture design. The impact of polyols (maltitol, lactitol, and xylitol) as sucrose replacers on the main quality properties of SFDC was determined. In the second stage, Saccharomyces boulardii was incorporated in the optimized formulation of SFDC as a probiotic product. Chocolates were stored at two temperatures (4 °C and 20 °C) for 180 days and the viability of probiotics was determined. The optimization data revealed that using 29.49 % maltitol, 51.46 % lactitol, and 19.05 % xylitol ended in the optimum SFDC with the highest desirability. The number of probiotics were retained at the functional amount after maintenance for 6 months. The highest probiotic viability was determined in the chocolates stored at 4 °C. The SFDCs possessing probiotics showed to be a promising sucrose-free functional chocolate.